Pengaruh Kompetensi dan Motivasi Kerja terhadap Produktivitas Kerja - M. Fachmi; Rosalia, Nirma; Nainggolan, Gilbert; Suhara, Ade; Hartono, Drajat (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The purpose of this study was to analyze the factors that influence the decision to purchase VIVA products. Samples were taken using purposive sampling technique. Analysis tools with multiple linear regression, hypothesis testing (t, F and coefficient of determination) and model accuracy testing. The results showed that there was a positive and significant influence both partially and simultaneously between e-WOM, Beauty Vlogger, Celebrity Endorser on the Decision to Purchase VIVA Products. The determination coefficient value of 0.716 means that e-WOM, Beauty Vlogger, Celebrity Endorser can influence the purchase decision of VIVA products by 71.6% and the remaining 28.4% is influenced by other variables.